Efficacy of intramyocardial injection of Algisyl-LVR for the treatment of ischemic heart failure in swine. (15th March 2018) - Choy, Jenny S.; Leng, Shuang; Acevedo-Bolton, Gabriel; Shaul, Semion; Fu, Lijuan; Guo, Xiaomei; Zhong, Liang; Guccione, Julius M.; Kassab, Ghassan S.
Abstract: Background: Progressive thinning and dilation of the LV due to ischemic heart failure (IHF) increases wall stress and myocardial oxygen consumption. Injectable biopolymers implanted in the myocardial wall have been used to increase wall thickness to reduce chamber volume, decrease wall stress, and improve cardiac function. We sought to evaluate the efficacy of a biopolymer (Algisyl-LVR) to prevent left ventricular (LV) remodeling in a swine model of IHF. Methods: IHF was induced in 11 swine by occluding the marginal obtuse branches of the left circumflex artery. Eight weeks later, Algisyl-LVR was injected into the LV myocardial free wall in five of the 11 animals. Echocardiographic examinations were done every 2 weeks for 16 weeks. Results: Within eight weeks of treatment, the ejection fraction increased from 30.5% ± 7.7% to 42.4% ± 3.5% (treated group) vs. 37.3% ± 3.8% to 34.3% ± 2.9% (control), p  < 0.01. Stroke volume increased from 18.5 ± 9.3 mL to 41.3 ± 13.3 mL (treated group) vs. 25.4 ± 2.3 mL to 31.4 ± 5.3 mL (control), p  < 0.05. Wall thickness in end-diastole of the infarcted region changed from 0.69 ± 0.06 cm to 0.81 ± 0.13 cm (treated group) vs. 0.73 ± 0.09 cm to 0.68 ± 0.11 cm (control), p  < 0.05. Sphericity index remained almost unchanged after treatment, although differences were found at the end of the study between both groups ( p  < 0.001). Average myofiber stress changed from 16.3 ± 5.8 kPa to 10.2 ± 4.0 kPa (treated group) vs. 15.2 ± 4.8 kPa to 17.9 ± 5.6 kPa (control), p  < 0.05. Conclusions: Algisyl-LVR is an effective strategy that serves as a micro-LV assist device to reduce stress and hence prevent or reverse maladaptive cardiac remodeling caused by IHF in swine.